Cell wall reconstruction and DNA damage repair play a key role in the improved salt tolerance effects of He-Ne laser irradiation in tall fescue seedlings. Issue 4 (2nd April 2016) - Gao, Limei; Li, Yongfeng; Han, Rong
Abstract: The improved salt tolerance effects of He–Ne laser were further studied through the estimation of ROS levels, cell viability, DNA damage phenomena, physicochemical properties, and monosaccharide compositions of cell wall polysaccharides in tall fescue seedlings. Salt stress produced deleterious effects on seedlings growth and development. ROS levels and genomic DNA damage were markedly increased compared with controls. Physicochemical activities and monosaccharide proportions of cell wall polysaccharide were also pronouncedly altered. He–Ne laser irradiation improved plant growth retardation via increasing cell viability and reverting physicochemical parameters. According to the results of Fourier transform infrared (FTIR) scanning spectra and DNA apopladder analysis, He–Ne laser was showed to efficiently ameliorate cell wall polysaccharide damage and DNA fragmentation phenomena. The treatment with DNA synthesis inhibitor further demonstrated that DNA damage repair was correlated with the improvement effects of the laser. Therefore, our data illustrated that He–Ne laser irradiation resulted in cell wall reconstruction and genomic DNA injury repair in vivo in salt-stressed seedlings, then enhanced salt tolerance probably via interactions between plant cell wall and related resistance gene expression pattern. Graphical abstract: : A proposed model regarding the improved salt resistance of He–Ne laser irradiation through modulating plant cell wall reconstruction and genomic DNA damage repair capacity.